Value co-creation or value co-destruction: co-production and its double-sided effect - Wu, Li-Wei; Rouyer, Ellen; Wang, Chung-Yu (International journal of bank marketing, 2022)
PurposeCo-production is an important process that alters value creation and improves the relationships between service providers and their customers. Such practice allows customers and service employees to access and leverage resources residing in their relationships. Clearly, the marketing-related literature focuses on the bright side of co-production. Nevertheless, the costs and potential negative consequences associated with its dark side must be further investigated. Therefore, this study aims to present a conceptual framework that explores the relationships among co-production, co-production enjoyment, co-production intensity, service effort, and job stress, and their effects on value co-creation, value co-destruction and customer satisfaction.Design/methodology/approachThis study was conducted on the basis of dyadic data; the process incorporates both the customer and the corresponding service employee into a single unit of analysis. The proposed model was tested by using a structural equation model that involves LISREL analyses.FindingsThe results of this study indicate that co-production influences co-production enjoyment, co-production intensity, service effort, and job stress. Co-production enjoyment and service effort increase value co-creation, whereas co-production intensity and job stress increase value co-destruction. Value co-creation and value co-destruction have different effects on customer satisfaction.Originality/valueThis study addresses the gap in the extant research and contributes to a better understanding of the double-sided effects of co-production by integrating employees and customers into a single dyadic and comprehensive model.